Pengaruh Motivasi Dan Komitmen Terhadap Kinerja Pegawai Negeri Sipil Di Dinas Kebudayaan Provinsi Bali - Ni Luh Fitria Asmara Dewi Yasa (Universitas Warmadewa, 2018)
This study aims to determine how much influence motivation and commitment to the performance of civil servants in the Department of Culture of Bali Province. Sampling The sample used in this study was all civil servants at the Bali Provincial Culture Office except the Head of the Bali Provincial Culture Office, so that as many as 92 people attended. In this study using the data used is primary data then continued with Path analysis or 'path analysis' with the help of the SPSS17.0 for Windows computer program. The results of the analysis show that motivation and commitment have a positive and significant effect on employee commitment, motivation and job satisfaction have a positive and significant effect on employee performance. To improve performance is still needed an increase in motivation and commitment. Increased motivation can be done by fulfilling the physiological needs of employees. Efforts to increase employee job satisfaction can be done by providing salaries in accordance with the position, class, years of service, education and most importantly seen from the workload that has been done by employees of the Bali Provincial Culture Office. Efforts to increase employee commitment can be done by providing understanding to employees about the objectives to be achieved by the agency by involving civil servants in every decision making agency.